Optimization of Tangerang Regency Mangrove Park as A Learning Resource for the Community (IJORER : International Journal of Recent Educational Research, 2026)
Objective: The Tangerang Regency Mangrove Park is a tourist attraction that offers numerous educational benefits to the community; however, the community has not been able to fully capitalize on these educational opportunities because visitors primarily engage in activities such as taking photos. Method: This study uses a quantitative approach, analyzing data using percentages, a Likert scale, and the 4A tourism object criteria (attractions, accessibility, facilities, and additional services). The data analysis techniques used were simple linear regression and a coefficient of determination summary model. Results: The results of the simple linear regression test indicate that the attractiveness of the mangrove park as a learning source (X) has a positive effect on tourist satisfaction (Y). The regression equation Y = 61.78 + 0.213X shows that when the attractiveness of the mangrove park as a learning resource increases by one unit, tourist satisfaction increases by 0.213 units, assuming all other variables remain constant. The coefficient of determination of 0.927 or 92.7% indicates that the variation in tourist satisfaction can be explained by the attractiveness of the mangrove park as a learning resource. Novelty: This research fills a crucial gap in mangrove ecotourism-based geography pedagogy, where existing studies have not integrated the 4A framework (attractions, accessibility, facilities, amenities) equivalent to the learning resource optimization model of messages, people, media, tools, techniques, and settings, through place-based education design in Tangerang Mangrove Park especially iconic landmarks such as I Love Mangrove, the circular bridge, and the bird's nest through a cycle of experience: observation, reflection, conceptualization, and application. This approach has not been explored.